"A true vassal of the King": Pardo literacy and political identity in Venezuela during the age of revolutions. Issue 3 (3rd July 2017) - Soriano, Cristina
ABSTRACT: Eighteenth-century Venezuela was a highly stratified society in which race, education, occupation, honor, family ties, and economic resources all played important roles in defining the place that each member occupied. In this complex social map, not all social groups had equal access to education; literacy was a marker of status and power. Traditionally, literate and formally educated people belonged to the white elite, while the majority of the supposedly "non-literate" population belonged to lower social groups of color, who relied largely on oral media for the transmission of knowledge. By the end of the eighteenth century, this picture began to change: the number of people who owned books increased, an incipient informal market of books began to operate, and original networks for the circulation of books and manuscripts among different social groups proliferated. Increasingly mixed-race groups, known as pardos, learned to read and write through informal means to an education. However, members of the colonial white elite interpreted pardos' access to literacy and education as a way of challenging the proper social order and authority. This article analyzes the case of Juan Bautista Olivares, a literate pardo musician who in 1795 was sent to court in Cádiz, accused by the Venezuelan governor of subversion; Olivares, however, successfully defended himself, declaring his loyalty to the Spanish Monarchy and proving his pious behavior. Pardos, like Juan Bautista, creatively navigated social tensions and the effects of the Atlantic Revolutions by shaping their political identity as royalists, questioning the local government and reasserting their loyalty to the Spanish Monarchy.